Investment under Rational Inattention: Evidence from US Sectoral Data - Peter Zorn (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Macroeconomic and sector-specific shocks exert differential effects on investment in disaggregate sectoral data. The response to macroeconomic shocks is hump-shaped, just as in aggregate data. The effects of sectoral innovations decrease monotonically. A calibrated model of investment with convex capital adjustment costs and rational inattention explains these features of the data. The model matches the empirical responses of sectoral investment because learning about shocks generates additional investment demand over time, and more so after aggregate shocks with relatively higher persistence. The interaction of information frictions and physical adjustment costs is key to this result.
Keywords: E22; E32; D25; D83; C38; 330; investment dynamics; hump shape; rational inattention; adjustment costs